2015
DOI: 10.1017/s135561771500079x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cardiorespiratory Fitness Is Associated with Increased Cortical Thickness in Mild Cognitive Impairment

Abstract: Objective Cortical atrophy is a biomarker of Alzheimer’s disease (AD) that correlates with clinical symptoms. This study examined changes in cortical thickness from before to after an exercise intervention in Mild Cognitive Impairment (MCI) and healthy elders. Method Thirty physically inactive older adults (14 MCI, 16 healthy controls) underwent MRI before and after participating in a 12-week moderate intensity walking intervention. Participants were between the ages of 61 and 88. Change in cardiorespiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
61
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 68 publications
10
61
0
2
Order By: Relevance
“…These findings extend a line of research in structural brain plasticity in clinical populations (Alosco et al., 2015; McEwen et al., 2015; Reiter et al., 2015; Sehm et al., 2014) by demonstrating training‐induced changes in cortical thickness in the context of cognitive training after TBI. Another novel component of our study is that we demonstrated structural plasticity following cognitive reasoning training, adding to similar evidence following physical activity (Alosco et al., 2015; McEwen et al., 2015; Reiter et al., 2015) and balance training (Sehm et al., 2014). Cognitive training regimes for TBI are frequently necessary to help individuals regain daily life functions, as individuals with chronic TBI often have persistent difficulties in the higher‐order cognitive domains, such as abstract reasoning, planning, decision making, and executive function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings extend a line of research in structural brain plasticity in clinical populations (Alosco et al., 2015; McEwen et al., 2015; Reiter et al., 2015; Sehm et al., 2014) by demonstrating training‐induced changes in cortical thickness in the context of cognitive training after TBI. Another novel component of our study is that we demonstrated structural plasticity following cognitive reasoning training, adding to similar evidence following physical activity (Alosco et al., 2015; McEwen et al., 2015; Reiter et al., 2015) and balance training (Sehm et al., 2014). Cognitive training regimes for TBI are frequently necessary to help individuals regain daily life functions, as individuals with chronic TBI often have persistent difficulties in the higher‐order cognitive domains, such as abstract reasoning, planning, decision making, and executive function.…”
Section: Discussionmentioning
confidence: 99%
“…(2010) observed that memory training reversed reductions in cortical thickness in older adults. Quantitative MRI‐based morphometry further revealed experience‐dependent brain plasticity in clinical populations such as balance training for Parkinson's disease (Sehm et al., 2014) and physical activity for heart failure, Schizophrenia, and mild cognitive impairment (Alosco et al., 2015; McEwen et al., 2015; Reiter et al., 2015). Training‐induced changes in resting‐state networks in the healthy adult brain have also been reported following motor training (Lewis, Baldassarre, Committeri, Romani, & Corbetta, 2009; Taubert, Lohmann, Margulies, Villringer, & Ragert, 2011), cognitive training (Jolles, van Buchem, Crone, & Rombouts, 2013; Mackey, Miller Singley, & Bunge, 2013; Takeuchi et al., 2013), and physical activity in the elderly (Voss, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…no specified criteria)[12, 32, 33], using one physiological variable (i.e. HR, RER)[13, 34, 35], or reporting some combination of variables [14, 36, 37]. For this project, we chose the ACSM guidelines because they provide an empirically established standard for CRF testing [28].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Coelho et al (2014) reported an increase in plasma BDNF levels in AD patients and healthy controls following a single bout of exercise on the treadmill, this result however was not accompanied by any cognitive testing. Also, recent neuroimaging data suggest that a 12 week moderate intensity walking intervention resulted in a thickening of the cortex, particularly in the left insula and superior temporal gyrus, in a cohort of patients displaying symptoms of mild cognitive impairment (Reiter et al, 2015). While these human studies give support to the data obtained from animal models, particularly with regard to exercise being a pro-cognitive intervention, future studies would undoubtedly benefit from adopting a multimodal approach and examine not only cognitive function, but also conduct neuroimaging to examine structural effects of exercise and biochemical analysis of blood samples to examine peripheral markers of inflammation and growth factors.…”
Section: Exercise In the Clinicmentioning
confidence: 99%